The Relationship Between Climate Change Issue Engagement, Connection to Nature and Mental Wellbeing - Matt Whelan; Shahin Rahimi-Golkhandan; Eric Brymer (Frontiers Media S.A., 2022)
As the threat of climate change becomes increasingly prevalent for people in both the developed and developing world, the impact of climate change on mental wellbeing has become a crucial area of research. In addition to the direct, indirect, and psychosocial impacts of climate change on mental wellbeing, there is also a question of how climate change driven changes to the environment will influence the well-established positive relationship between connection to nature and mental wellbeing. The aim of this study was to investigate the relationship between climate change issue engagement, connection to nature, and mental wellbeing in English speaking adults over 18 years of age. This study examined the average levels of connection to nature and mental wellbeing in people with different levels of climate change issue engagement, and evaluated whether a person's level of climate change issue engagement uniquely predicted mental wellbeing. The study corroborated positive relationships between wellbeing and various aspects of relatedness to nature in the overall sample. The strength of these relationships, however, depended on the level of climate change issue engagement. More specifically, the level of engagement is inversely linked to mental wellbeing, such that the lower the level of engagement, generally the higher is wellbeing.